Disruption of microfilament organization in living nonmuscle cells by microinjection of plasma vitamin D-binding protein or DNase I. - Sanger, J M (1990)
Plasma vitamin D-binding protein (DBP), which binds to monomeric actin, causes the breakdown of stress fibers when it is microinjected into nonmuscle cells. Disruption of the stress fiber network is also accompanied by shape changes in the cell that resemble those seen after cytochalasin treatment. When DBP was coinjected with fluorescently labeled alpha-actinin, no fluorescent stress fibers or attachment plaques were visible 30 min after injection. Twelve hours later the cells regained their flattened shape and their stress fibers. Fluorescently labeled DBP causes the same reversible changes in cell shape as the unlabeled protein. Upon injection, the labeled DBP diffuses throughout the cytoplasm, becoming localized by 12 hr in a punctate pattern, presumably due to lysozomal sequestration. Similar injections of DBP into skeletal myotubes and cardiac myocytes did not lead to shape changes or breakdown of nascent and/or fully formed myofibrils, even though DBP has a 2-fold higher binding affinity for muscle actin over that of the nonmuscle isoactins. Similar differential effects in nonmuscle cells were also observed after the microinjection of DNase I, another protein capable of binding monomer actin. The effects of these microinjected monomer actin-binding proteins imply that an accessible pool of monomer actin is needed to maintain stress fiber integrity in nonmuscle cells but not the integrity of the nascent or fully formed myofibrils in muscle cells.